Giant Resin Bee Megachile sculpturalis (Smith) (Insecta: Hymenoptera: Megachilidae) - Kristen C. Stevens; Cameron Jack; James D Ellis (EDIS)
Originally from eastern Asia, the giant resin bee, Megachile sculpturalis (Smith), was accidentally introduced into the United States in the 1990s. It is considered an adventive (not native and usually not established) species and is present in most states in the eastern US. Although these bees can be found on various plants, they typically prefer plants that have been introduced from their native area. Some have observed that when collecting pollen or nectar, Megachile sculpturalis will damage local flora, making it unusable to future bee visitors. However, evidence has shown that, although an adventive species, Megachile sculpturalis is thought to be a pollinator of a native and federally threatened plant, the Apios Pricenana. https://edis.ifas.ufl.edu/in1258